Avaliação da sustentabilidade de um sistema de produção de cana-de-açúcar orgânica - Ariedi Junior, Vagner Roberto (Universidade Federal de São Carlos, 2013)
This work aimed to bring a summary of all the actions and practices of organic farming and differential ecological management in a production system of sugarcane. Extensive literature review, consultation with specialized technical and scientific collections, observations and field inspection, were used. Available information were analyzed, such as documents, diagnoses, reports, primary and secondary data. The results of the actions and practices implemented were positive and beneficial in the environmental, economic and social spheres, unlike those practiced in conventional systems. The evaluated system showed up important and effective in the recovery, conservation and biodiversity maintenance, beyond showed up as minimization instrument of social impacts associated with the sector. The system showed a higher level of sustainability when compared to conventional.
Assessment of sustainability of a production system of organic sugarcane
Keywords: Agroecologia; Agricultura; Agroecossistemas; Agricultura sustentável; Agricultura orgânica; Setor sucroalcooleiro; CIENCIAS AGRARIAS